ALOKASI REMITANSI PENDAPATAN KELUARGA MIGRAN DI KECAMATAN LANGOWAN UTARA - Junita ., Rantung; Celcius ., Talumingan; Ellen G. Tangkere (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the allocation of remittance of migrant family income in North Langowan Subdistrict. This study uses descriptive analysis, by conducting surveys or field observations todetermine the utilization of remittances by the families of migrant workers. The research was conducted in February to May 2018 in North Langowan Subdistrict, in Walantakan Village, Toraget Village,Karumenga Village, Taraitak Village and Taraitak Village 1. The method used in this research is survey method by taking primary data and secondary data. Primary data collection is intended to know the clear picture of the utilization of Indonesian labor remittances for consumption, investment and savings or for agriculture or not. The primary data collection technique was carried out by direct interviews and the questionnaire distributed to the families of migrant workers regarding the pattern of money managementof remittances. Secondary data was obtained from North Langowan Subdistrict office. The results of this study indicate that most migrants allocate remittances to renovate houses or buy land / houses, from which 40% to 50% of the remuneration is used for the allocation. Some of the migrants make use of remittances to buy houses for investment and partly to finance children's education. Some of the migrants use remittances to buy rice fields as another form of investment, and only a small percentage of migrantsmake use of remittances to buy cars as a tertiary family need. Remittance remained for savings. Migration in addition to affecting the increase in income and welfare of migrant families also affects the development of land prices in North Langowan Subdistrict.*er*